Rol profesional del Diseñador Gráfico en el contexto social actual - Naula Asitimbay, David Eduardo (2026)
At present, the graphic designer has not been fully recognized as a true profession and is often undervalued. In this regard, the research addresses the professional role of the graphic designer within the current social context, analyzing how it responds to the professional environment based on academic training. For this purpose, a comparative analysis was conducted of the academic curricula, graduate profiles, and competencies of four higher education institutions in Ecuador: Universidad Técnica de Ambato, Universidad Nacional de Chimborazo, Universidad de las Américas, and Instituto Metropolitano de Diseño. The study adopted a qualitative approach with an exploratory descriptive research design. Data were collected through semi-structured interviews conducted with both recent and former graduates of the Graphic Design program. The results reveal a gap between current labor market demands and the education received during university studies, particularly in areas such as digital tools, user experience, and artificial intelligence. Finally, the study concludes that educational programs should be restructured from a more professional-oriented perspective, incorporating content directly aligned with real world professional practice and promoting the graphic designer as an agent of cultural and communicational change.